2016
DOI: 10.1038/ncomms12526
|View full text |Cite
|
Sign up to set email alerts
|

Temporal regulation of Lsp1 O-GlcNAcylation and phosphorylation during apoptosis of activated B cells

Abstract: Crosslinking of B-cell receptor (BCR) sets off an apoptosis programme, but the underlying pathways remain obscure. Here we decipher the molecular mechanisms bridging B-cell activation and apoptosis mediated by post-translational modification (PTM). We find that O-GlcNAcase inhibition enhances B-cell activation and apoptosis induced by BCR crosslinking. This proteome-scale analysis of the functional interplay between protein O-GlcNAcylation and phosphorylation in stimulated mouse primary B cells identifies 313 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 41 publications
(47 reference statements)
3
48
0
Order By: Relevance
“…For example, phosphorylation is important for Daxx in sensitizing stress-induced apoptosis (17). Similarly, phosphorylation of LSP1 S243 is critical for triggering B lymphocyte apoptosis (18). Interestingly, when we checked the expression levels of proapoptosis (Bim, Bax, Bad) and antiapoptosis (Bcl2, Bcl-xl) proteins (19), no obvious differences were observed between WT (Lck-Cre + ) and cKO (Lck-Cre + Ppp2ca flox/flox ) thymocytes, in either unstimulated cells or cells stimulated with anti-CD3 (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For example, phosphorylation is important for Daxx in sensitizing stress-induced apoptosis (17). Similarly, phosphorylation of LSP1 S243 is critical for triggering B lymphocyte apoptosis (18). Interestingly, when we checked the expression levels of proapoptosis (Bim, Bax, Bad) and antiapoptosis (Bcl2, Bcl-xl) proteins (19), no obvious differences were observed between WT (Lck-Cre + ) and cKO (Lck-Cre + Ppp2ca flox/flox ) thymocytes, in either unstimulated cells or cells stimulated with anti-CD3 (SI Appendix, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Golks et al [23] showed that induced O-GlcNAcylation of nuclear factor-kappa B (NF-κB) and nuclear factor of activated T cells (NFAT) is required for T-and B-lymphocyte activation. Additionally, the critical interplay between O-GlcNAcylation and phosphorylation for lymphocyte-specific protein-1 (Lsp-1) during B cell activation was proposed as a novel regulatory mechanism to explain how B cells control survival or apoptotic fate after BCR cross-linking [24]. Moreover, genetically engineered mouse models in which Ogt can be deleted at differential stages of B cell development showed not only defective activation of BCR signaling but also significant disruption of B cell homeostasis by enhancing apoptosis of germinal center B cells and memory B cells, which eventually resulted in reduced production of antibodies following immunization [25].…”
Section: Introductionmentioning
confidence: 99%
“…45 It is not known if Lsp-1 in neutrophils is influenced by O-GlcNAcylation, but this protein, as alluded to before, requires O-GlcNAcylation at serine 209 for serine 243 phosphorylation and subsequent F-actin interactions in murine B cells. 29 A more extensive analysis of overall O-GlcNAcylation levels in human neutrophils by flow cytometry and fluorescence microscopy also showed increased O-GlcNAcylation following fMLP stimulation when compared with unstimulated controls. 46 Although these results indicate that neutrophil chemotaxis is positively dependent on O-GlcNAcylation, there also is a study which found an inhibitory effect of GlcN treatment on human neutrophil chemotaxis and fMLP-driven F-actin interactions.…”
Section: O-glcnacylation In Bacterial Infectionsmentioning
confidence: 90%
“…This binding subsequently results in apoptosis as a consequence of reduced Bcl-2 and Bcl-X L expression. 29 Hence, O-GlcNAcylation is also involved in apoptosis of activated B cells. Lastly, the O-GlcNAcylation of EZH2 may also be of importance in humoral immunity against viral infections.…”
Section: O-glcnacylation In Viral Infectionsmentioning
confidence: 99%
See 1 more Smart Citation